2011
DOI: 10.1163/092050609x12587018007767
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and Osteogenic Capacity of Periodontal Ligament Stem Cells on nHAC/PLA and HA/TCP Scaffolds

Abstract: This study investigated the effects of a newly-developed scaffold, nano-hydroxyapatite/collagen/poly(L-lactide) (nHAC/PLA), on the attachment, proliferation and osteogenic capability of dog periodontal ligament stem cells (PDLSCs) in vitro and in vivo. Hydroxyapatite/tricalcium phosphate (HA/TCP), a commonly used bone substitute, was used as a positive control. PDLSCs isolated from dog molar were incubated in an osteogenic medium to evaluate their osteogenic differentiation in vitro, and then seeded onto nHAC/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 33 publications
1
42
0
Order By: Relevance
“…As an increasing number of PDLSC studies have been conducted, STRO-1, CD146 and other mesenchymal stem cell surface markers and certain perivascular cell surface markers, such as CD105, CD106 and CD166, have been widely recognized. The STRO-1 antibody immunomagnetic or the flow cytometry separation methods are commonly known to be the most effective separation methods for PDLSCs (4,(20)(21)(22)(23). In the present study, STRO-1 + cells were separated by flow cytometry and preliminary identification indicated that these cells possess high self-renewal capacity and multi-lineage differentiation potential.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…As an increasing number of PDLSC studies have been conducted, STRO-1, CD146 and other mesenchymal stem cell surface markers and certain perivascular cell surface markers, such as CD105, CD106 and CD166, have been widely recognized. The STRO-1 antibody immunomagnetic or the flow cytometry separation methods are commonly known to be the most effective separation methods for PDLSCs (4,(20)(21)(22)(23). In the present study, STRO-1 + cells were separated by flow cytometry and preliminary identification indicated that these cells possess high self-renewal capacity and multi-lineage differentiation potential.…”
Section: Discussionmentioning
confidence: 61%
“…(4,20,21). Briefly, periodontal ligament tissues were scraped from the intermediate 1/3 of the root.…”
Section: Introductionmentioning
confidence: 99%
“…The nHAC/PLA scaffold has good biocompatibility and osteoconductive capacity [40]. It was formed from new mineralized collagen consisting of a combination of collagen fibrils and PLA attached to nanohydroxyapatite by a self-assembly method.…”
Section: Discussionmentioning
confidence: 99%
“…These studies revealed the regeneration of normal periodontal tissues, containing organized cementum, alveolar bone and the PDL attachment apparatus. The possibility of constructing a root-periodontal tissue complex was further successfully demonstrated using a pelleted hydroxyapatite/tricalcium phosphate scaffold containing SCAP, coated with PDLSC-seeded Gelfoam, implanted and grown in minipig tooth socket (11,41). The multipotent differentiation properties of PDLSC for generating both hard and soft tissues were further demonstrated by constructing multilayered cell sheets supported by woven polyglycolic acid.…”
Section: Dental Pulp Stem Cells and Dental Tissue Engineeringmentioning
confidence: 99%